The Analysis Study of Effectiveness and Safety of Rituximab in The Management of Pediatric Systemic Lupus Erythematosus: A Systematic Review - Muhammad Ilham Wira Tri Putra; Asra Dewita Namora Harahap (International Medical Journal Corp. Ltd, 2025)
Background: Pediatric systemic lupus erythematosus (pSLE) is a chronic autoimmune disease with an incidence of 0.3–0.9 per 100,000 children per year. Despite growing interest in RTX as a therapeutic option, its use in pSLE remains off-label, and its efficacy and safety have not been well established in this population. This systematic review aims to assess the effectiveness and safety of RTX in children with pSLE based on literatures of the last decade. Methods: The study followed PRISMA 2020 guidelines, reviewing English-language publications from 2015 to 2025. Editorials, duplicate reviews from the same journal, and papers lacking a DOI were excluded. The literature search was conducted using PubMed, SagePub, SpringerLink, and Google Scholar. Result: A total of 2,172 articles were initially identified through online databases (PubMed, SagePub, SpringerLink, and Google Scholar). After three rounds of screening, eight relevant studies were selected for full-text analysis. Conclusion: Rituximab is an effective and well-tolerated treatment for pediatric SLE, reducing disease activity, corticosteroid dependence, and flare-ups. While generally safe, monitoring for infusion reactions and hypogammaglobulinemia is crucial. Early administration may improve outcomes, highlighting its role in refractory pediatric SLE management.